Contribución al estudio fitoquímico de plantas costarricenses. I. Análisis Alcaloidal - Sáenz R., José A. (1964)
A total of 59 species of Costa Rica plants have been tested for terciary and quaternary bases. The presence of alkaloids in the following plants: Stemmadenia glabra Benth.; Crotalaria mysorensis Roth.; Tournefortia glabra L. y Melochia pyramidata L. is reported for the first time. Alkaloids are shown to be absent in several other plants used in foLk medicine in Costa Rica.